2018
DOI: 10.1097/md.0000000000013059
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy diagnosis of acupuncture-induced bilateral tension pneumothorax using whole-body postmortem computed tomography

Abstract: Rationale:Acupuncture, a component of traditional Chinese medicine, is also a well-known form of complementary and alternative medicine. Serious adverse events of acupuncture have been reported, including the acupuncture-related pneumothorax which is a rare but fatal condition sometimes. The pneumothorax was related to needle insertion in the upper back or paraspinal area and the reported victims suffered from either unilateral or bilateral pneumothorax. Postmortem computed tomography has advantages in the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…It is generally considered unlikely that a single lung perforation with a fine needle will cause rapid respiratory failure in a healthy population. However, previous reports have suggested that multiple bilateral lung punctures can lead to fatal bilateral tension pneumothoraces, even in the absence of a significant pulmonary disease background (15–18). As in this case, lung diseases, such as emphysema, are risk factors for the development of pneumothorax after acupuncture (11,14,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally considered unlikely that a single lung perforation with a fine needle will cause rapid respiratory failure in a healthy population. However, previous reports have suggested that multiple bilateral lung punctures can lead to fatal bilateral tension pneumothoraces, even in the absence of a significant pulmonary disease background (15–18). As in this case, lung diseases, such as emphysema, are risk factors for the development of pneumothorax after acupuncture (11,14,16).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of a three‐dimensional reconstruction image of PMCT depicting the distribution of gold thread acupuncture throughout the body. PMCT has an advantage over conventional autopsy in that it is better at depicting gas collections in the body and metallic substances, such as implanted medical artifacts; thus, it is widely used as a routine procedure before autopsy in many institutes (18,30–32). This case demonstrates the usefulness of PMCT and presents an unusual PMCT image finding that requires attention in assessing its relevance to the cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic pneumothorax has not been regarded to date as a topic of special interest or a subject of more in-depth research in the field of forensic medicine. The basic aspects of the problem have been discussed in academic textbooks, and casuistic reports from the field of post-mortem research have appeared in a limited number of publications [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…Tabela II. Zestawienie procentowego udziału poszczególnych obrażeń i zespołów obrażeń klatki piersiowej w grupie przypadków ze stwierdzoną odmą opłucnową (n = 195) omawiana w podręcznikach akademickich, a nieliczne publikacje prezentowały kazuistyczne doniesienia z praktyki badań pośmiertnych [2,8]. Znacznie więcej opracowań można znaleźć w obszarze nauk klinicznych, w szczególności medycyny ratunkowej i traumatologii [9][10][11][12][13][14][15][16][17].…”
Section: Discussionunclassified
See 1 more Smart Citation